Northern Territory Aboriginal communities (Dept. of Lands, Planning and Environment], 1996)
Lists Northern Territory communities in alphabetical order , numerical order, alphabetical by council or resource centre name and by alternate name; gives latitude and longitude and reference to ATSIC council.